(3fRgI GdCHUGQ aj eMGSf GdCTYGQs - (3GdHgGA RgjQ , RgjQ Hf eMeO Hf Ydj GdegdHj GdUGdMj, HgGA GdOjf,J (B656 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd EMSGfg hYWGjGg CeG HYO CeQJ CYdG Gddg CeQc aCLHJc Edi eG Zdjg CTQJ hLeYJ ai gPG GdcJGH ef ebWYGJ GdBOGH s
(3BNQgG (B:s
(3Cf CfcQ WQag Lhi eZQeg eY QTa eOGe aGdhLfI YfOejI Yf Oeg JUOjb cdGe gPG BNQ eG hOJg ef gPG GdcJGH s
(3YdjgG Jedc SfI (B1166s
(3Cdag UGMHg ddCejQ TLGY GdOjf hbSeg Edi SHYI CHhGH hVefg ebJWaGJ ef GdTYQ ai GdaVGFd hGdENhGFjGJ hGdeaGcgI h GdecGJHGJ hGdMce hGdYdhe hWHbGJ GdfGS hHYV GdedM GdZQjHHI hGdWQGFa hGdfhGOQ hGdThGOQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B52s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs